The Upregulation of COX2 in Human Degenerated Nucleus Pulposus: The Association of Inflammation with Intervertebral Disc Degeneration - Chang Liu; Guoyan Liang; Zhantao Deng; Jing Tan; Qiujian Zheng; Feng-Juan Lyu (Mediators of Inflammation)
Intervertebral disc degeneration (IVDD) is an important risk factor of low back pain. We previously found upregulated markers of fibrosis, the late stage of chronic inflammation, in degenerated IVD with a small number of clinical specimens. Here, we aimed to study on a larger scale the association of cyclooxygenase 2 (COX2), an inflammation and/or pain marker, with IVDD. This study involved 107 LBP participants. The IVD degeneration level was graded on a 1–5 scale according to the Pfirrmann classification system. Discs at grades 1-3 were further grouped as white discs with grades 4-5 as black discs. We recorded baseline information about age, gender, body mass index (BMI), diabetes history, smoking history, and magnetic resonance imaging (MRI). Their association with IVDD was statistically analyzed. The expression level of COX2 was investigated by immunohistochemistry. The total integrated COX2 optical density (IOD), number of COX2-positive cells, and total cell number of each image were counted and analyzed by Image-Pro Plus software. The IOD and number of COX2-positive cells were divided by the total cell number to obtain COX2 expression density (IOD/cell) and COX2 positivity (cell+/cell). As a result, among the baseline information investigated, only age was found to have a significant association with IVDD. The IOD/cell was found to be significantly increased from grade 2 to grade 5, as well as in black discs compared to white discs. The cell+/cell displayed the same trend that it increased in highly degenerative discs compared to their counterparts. In conclusion, the expression of COX2 is associated with IVDD, which highlights COX2 as a biomarker for IVD degeneration and indicates the involvement of inflammation and pain signaling in IVDD.